Altered B-lymphopoiesis in mice with deregulated thrombopoietin signaling. Issue 1 (December 2017) - Au, Amanda; Lebois, Marion; Sim, Starling; Cannon, Ping; Corbin, Jason; Gangatirkar, Pradnya; Hyland, Craig; Moujalled, Diane; Rutgersson, Angelika; Yassinson, Fatme; Kile, Benjamin; Mason, Kylie; et al.
Abstract Thrombopoietin (TPO) is the master cytokine regulator of megakaryopoiesis. In addition to regulation of megakaryocyte and platelet number, TPO is important for maintaining proper hematopoietic stem cell (HSC) function. It was previously shown that a number of lymphoid genes were upregulated in HSCs fromTpo −/− mice. We investigated if absent or enhanced TPO signaling would influence normal B-lymphopoiesis. Absent TPO signaling inMpl −/− mice led to enrichment of a common lymphoid progenitor (CLP) signature in multipotential lineage-negative Sca-1+ c-Kit+ (LSK) cells and an increase in CLP formation. Moreover, Mpl −/− mice exhibited increased numbers of PreB2 and immature B-cells in bone marrow and spleen, with an increased proportion of B-lymphoid cells in the G1 phase of the cell cycle. Conversely, elevated TPO signaling inTpo Tg mice was associated with reduced B-lymphopoiesis. Although at steady state, peripheral blood lymphocyte counts were normal in both models, Mpl −/− Eµ-myc mice showed an enhanced preneoplastic phase with increased numbers of splenic PreB2 and immature B-cells, a reduced quiescent fraction, and augmented blood lymphocyte counts. Thus, although Mpl is not expressed on lymphoid cells, TPO signaling may indirectly influence B-lymphopoiesis and the preneoplastic state inMyc -driven B-cell lymphomagenesis by lineage priming in multipotential progenitor cells.